Peloton's safety issues - Robson, Karen, (SAGE Business cases., 2021)
Months after learning of safety concerns related to the Peloton treadmill, Tread+, Peloton issued a product recall. This case covers Peloton’s initial reactions to the safety concerns, subsequent product recall, and brand position in the months after the recall. Students are asked to evaluate Peloton’s reaction to the safety concerns, and to brainstorm what the company should do moving forward to ensure that they are positioned in a desirable way.